Antiplatelet therapy for secondary prevention in patients with ischaemic stroke and transient ischaemic attack: a retrospective cohort study in Malaysia - Ab Rahman N; Law Wc; Pang SHL; Wong WY; Sivasampu S (Penerbit UKM, 2023)
In this study, we evaluated clinical outcomes of antiplatelet therapy for secondary prevention in ischaemic stroke and transient ischaemic attack (TIA) patients. This was a retrospective cohort study that included patients with newly diagnosed ischaemic stroke or TIA between 2014 and 2017 using data from routine practice in Malaysia. Patients were grouped into single antiplatelet therapy (SAPT) and dual antiplatelet therapy (DAPT) users. Primary outcome was composite of stroke, myocardial infarction, and all-cause death in 90 days and 1 year. Safety outcome was major bleeding events. Among 3344 stroke patients, 8.1% received DAPT and 91.2% received SAPT. The 1-year cumulative incidence of composite events was 16.0 and 7.2 per 100 person-years for SAPT and DAPT, respectively. Propensity score-matched analysis of Cox hazard model showed DAPT reduced the risk of composite event (hazard ratio (HR) 0.48; 95% CI 0.25-0.91) and recurrent stroke (HR 0.38; 95% CI 0.16-0.92) in 1-year follow-up. Results were not significant for myocardial infarction, all-cause death, and 90-day outcomes. The risks of bleeding were not significantly different between SAPT and DAPT. Treatment with DAPT after an ischaemic stroke/TIA was associated with reduced risk of the composite events (stroke, myocardial infarction, or death) and recurrent stroke at 1 year.